Feed the future aquaculture project: Annual report: October 2011-September 2012 - WorldFish (WorldFish, 2012)
The Feed the Future Aquaculture project is a five year transformative investment in aquaculture focused on 20 southern districts in Barisal, Khulna and Dhaka divisions, Bangladesh. This report describes the achievements of FtF-Aquaculture project activities implemented during FY12. Some of the targets for production and associated income have not been achieved yet as a large share of the fish will be harvested after closing of the reporting period. However, on the basis of growth monitoring, indications are that production is on track to achieve the targets.